1999
DOI: 10.1046/j.1365-8711.1999.02772.x
|View full text |Cite
|
Sign up to set email alerts
|

Excitation and kinematics in H2 bow shocks: near-infrared observations of HH 99 and VLA 1623A (HH 313)

Abstract: We present a comprehensive near‐infrared study of two molecular bow shocks in two protostellar outflows, HH 99 in R Coronae Australis and VLA 1623A (HH 313) in Rho Ophiuchi. New, high‐resolution, narrow‐band images reveal the well‐defined bow shock morphologies of both sources. These are compared with two‐dimensional MHD modelling of molecular bows from which we infer flow inclination angles, shock speeds and the magnetic field in the pre‐shock gas in each system. With combined echelle spectroscopy and low‐res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
49
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 43 publications
13
49
1
Order By: Relevance
“…Partially responsible for the large spread might be the fact that the actual extinction curve is different from the one used here. Extinction values for extended regions of the ρ Oph cloud and as high as those derived here have been reported also by others (e.g., Davis et al 1999;Whittet et al 2008). Especially remarkable, and in line with our own findings, is the result of Davis et al (1999) for HH 313A, who found at 0 · 6 resolution variations of the K-band extinction by 3 mag (ΔA V = 30 mag) over only 6 , i.e., the size of one CAM pixel.…”
Section: T N(hsupporting
confidence: 91%
See 2 more Smart Citations
“…Partially responsible for the large spread might be the fact that the actual extinction curve is different from the one used here. Extinction values for extended regions of the ρ Oph cloud and as high as those derived here have been reported also by others (e.g., Davis et al 1999;Whittet et al 2008). Especially remarkable, and in line with our own findings, is the result of Davis et al (1999) for HH 313A, who found at 0 · 6 resolution variations of the K-band extinction by 3 mag (ΔA V = 30 mag) over only 6 , i.e., the size of one CAM pixel.…”
Section: T N(hsupporting
confidence: 91%
“…Comparing to the data of Table 3, a beam filling below the 10% percent level would be indicated, which would correspond to linear source sizes of the order of 20 . This is not unreasonable, as small scale structure is observed in ro-vibrationally excited H 2 emission (Dent et al 1995;Davis et al 1999;Caratti o Garatti et al 2006), and also in [S II] lines from HH 313 (Wilking et al 1997;Gómez et al 2003;Phelps & Barsony 2004). …”
Section: Compact High-density Gas and Standard O-abundancementioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, near-infrared (H 2 2.12 µm) imaging observations have detected and explored shock-excited knots and jets located in highly obscured areas (Davis & Eisloeffel 1995;Dent et al 1995;Davis et al 1999;Grosso et al 2001). These searches have been confined to small regions, typically 5 × 5 .…”
Section: Introductionmentioning
confidence: 99%
“…3 from B are detected (Bb1 and Br1 knots). We note that, assuming an inclination angle with respect to the line of sight of 75 • as for the A outflow (Davis et al 1999), the maximum projected velocities of 14 km s −1 (with respect to the ambient systemic velocity of 3.6 km s …”
Section: Resultsmentioning
confidence: 99%